APPLICATION OF LEAN-KAIZEN CONCEPT FOR IMPROVING QUALITY SYSTEM OF MANUFACTURING FIRMS - Kumar, Sunil; Dhingra, Ashwani Kumar; Singh, Bhim (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This research paper demonstrates a case study of improving the quality system for ten small and medium-size fastener manufacturing industries by applying the Lean-Kaizen using data envelopment analysis (DEA) technique. The data has been composed by paying personal visits to the selected industries over three months for primarily two inputs (manpower and quality cost) and one output (on-time delivery). The efficiency score of the selected industries has been calculated through the constant returns to scale (CRS), Charnes Cooper & Rhodes (CCR) model having the most efficient industry as a benchmark. The input minimization is considered an objective function to explore the possibilities of input reduction. The Lean-Kaizen concept was to identify the slackness/ gap areas within the inputs with the 5-why method for eliminating the waste and identifying the root cause of the gap areas and Kaizen events. After applying the Kaizen events, the DEA CCR model has been used to analyze the collected data with improvement in efficiency score as findings for the selected industries. Out of ten selected industries,100% efficiency in the quality system has been reported in two industries with 9% to 52% enhancement in others. The study will be helpful to the managers and academicians to overcome the different inefficiencies in the organizations.